Tourism planning and development of local government units: A bibliometric analysis - Uy, Ingrid; Sarsale, Melvin (Hotel and Tourism Management, 2026)
Purpose – This study examines research on tourism planning and development involving local government units (LGUs), focusing on publication trends, intellectual structure, major contributors, and emerging themes. Methodology – To address these aims, a bibliometric analysis was conducted on 468 Scopus-indexed journal articles published from 1976 to 2026. The analysis examined publication output, citation performance, leading countries, institutions, journals, authors, and influential papers. It also mapped collaboration patterns and thematic trends using co-authorship, keyword co-occurrence, clustering, and trend analysis. Findings – Research output has increased markedly since the mid-2010s, indicating growing scholarly attention to LGU-related tourism planning and development. Scholarly influence remains concentrated in a few countries and institutions. Core themes include the role of local government, stakeholder participation, and sustainability, while emerging topics involve tourism management, spatial-temporal analysis, visitor management, and recovery from disruptions. Implications – For LGU practitioners, these findings highlight the need for stakeholder engagement, data-driven planning, stronger institutional frameworks, and tourism policies that support sustainability and resilience. Further research may compare local government policies, governance approaches, and tourism development across contexts. However, the results should be interpreted in light of the study’s limitations, including reliance on Scopus and bibliometric methods.